KONTEN KREATOR YOUTUBE SEBAGAI SUMBER PENGHASILAN (Telaah Kritis Hukum Ekonomi Syari’ah) - Arif Hariyanto; Aditya Putra (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2022)
YouTube is a social media that is in demand by many people of all age groups. Because of this, many people make YouTube a source of income. The way to make money from YouTube or called the Monetization system, requires YouTubers to enter into a cooperation agreement with the YouTube Partner Program. YouTubers who have made a contract by agreeing to all the rules from the YouTube Partner Program, but in practice they often violate these rules, in practice sometimes many YouTubers whose content violates Islamic Sharia and violates the rules of the YouTube community. The final conclusion from this research according to the Sharia Economic Law Perspective on creator content income on the YouTube Channel is allowed, because the agreement made by YouTubers and the YouTube Partner Program is with the pleasure of YouTubers by agreeing to the terms made by the YouTube Partner Program by clicking